Life Cycle Assessment of Three Municipial Solid Waste Management Scenarious in Istanbul - Cetinkaya, Afsin Y.; Bilgili, Levent (Mehmet Sinan Bilgili, 2022)
Industrialization and rapid population growth increase the production of solid waste and cause negative effects on the environment. Since this waste must be disposed of safely, landfills are important. The increase in industrialization and urbanization has caused problems such as increased energy demand, bulky waste generation and environmental impacts. Municipial solid waste (MSW) has a negative impact on human and environmental health. Solid waste management is directly or indirectly affected by government policies and the development of economy and technology. To this end, life cycle assessment (LCA) provides information on environmental impacts associated with waste disposal methods. Three different scenarios were applied for municipial solid waste management for their impact on energy production and the environment. LCA results also showed that scenario 2 (Combustible wastes are sent to incineration, others are sent to Landfill) among all scenarios has the lowest environmental burden level in terms of global warming, freshwater and marine ecotoxicity and non-carcinogenic human.
Keywords: Life cycle Assesment; Municipial Solid Waste; Engineering; Environmental Sciences & Ecology